EKSPLORASI JAMUR YANG DIKONSUMSI DI HUTAN DESA HUNITETU KECAMATAN INAMOSOL KABUPATEN SERAM BAGIAN BARAT - Haryanto, Muhammad Hijril Ismail; Sahupala, Andjela; Hadijah, Miranda H. (MARSEGU : Jurnal Sains dan Teknologi, 2026)
Tropical forest ecosystems in Indonesia are known for their high biodiversity, including fungi that play important ecological roles and have potential as food resources. However, wild edible mushrooms remain underexplored and poorly documented. This study aims to explore and identify edible mushroom species found in Hunitetu Village, Inamosol District, West Seram Regency, and to classify them based on their morphological characteristics and growth habitats. The method used was a descriptive exploratory approach through surveys and direct observations in various potential locations, including forests, gardens, agricultural lands, and areas surrounding settlements. Each mushroom sample found was documented and identified based on macroscopic morphological characteristics, including the shape and color of the cap (pileus), stalk (stipe), surface texture, and growth substrate. The results showed that all collected mushroom samples were successfully identified in detail according to their morphological characteristics. Based on the observations, two species were identified as edible mushrooms, while the remaining species were categorized as non-edible. Overall, these findings provide preliminary information on the diversity of edible mushrooms in the study area and highlight their potential for sustainable utilization as non-timber forest products.